2019
DOI: 10.3389/fchem.2019.00856
|View full text |Cite
|
Sign up to set email alerts
|

Structural Design, Synthesis, and Preliminary Biological Evaluation of Novel Dihomooxacalix[4]arene-Based Anti-tumor Agents

Abstract: Calixarene and its derivatives have extensively served as promising anti-tumor agents. Previously, we have synthesized a series of calix[n]arene polyhydroxyamine derivatives (n = 4, 6, 8) and found that 5,11,17,23-tetra-tert-butyl-25,27-bis [N-(2-hydroxyethyl)aminocarbonylmethoxyl] calix[4]arene (CLX-4) displayed significant effect toward SKOV3, A549, SW1990, HeLa, Raji, and MDA-MB-231 cancer cells. In the present work, we find a replacement of calix[4]arene bone and synthesized 19 novel structurally related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…They found that some of the calixarenes were able to prevent breast cancer development cancer cells and induce apoptosis in these cells. Another study investigated the activity of calixarenes against human colon cancer cells and found that the compounds were able to inhibit the growth of these cells and induce apoptosis through the caspase pathway 29,30 . In addition to their ability to induce apoptosis, calixarenes also have the potential to enhance the efficacy of other anti-cancer agents.…”
Section: Introductionmentioning
confidence: 99%
“…They found that some of the calixarenes were able to prevent breast cancer development cancer cells and induce apoptosis in these cells. Another study investigated the activity of calixarenes against human colon cancer cells and found that the compounds were able to inhibit the growth of these cells and induce apoptosis through the caspase pathway 29,30 . In addition to their ability to induce apoptosis, calixarenes also have the potential to enhance the efficacy of other anti-cancer agents.…”
Section: Introductionmentioning
confidence: 99%
“…Pillar [n]arenes (Ogoshi et al, 2008;Xiao et al, 2018;Duan et al, 2020;Wang et al, 2020;Wang et al, 2022b) are the fifth generation of macrocyclic hosts following crown ethers (An et al, 2021), cyclodextrins (Zhou et al, 2021), calixarenes (An et al, 2019;Guo et al, 2020b) and cucurbiturils (Yan et al, 2021). They are oligo-cyclic compounds obtained by methylene bridged p-methoxylbenzene (Zhang et al, 2019;Lou and Yang, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, calixarenes have been proven to be good building scaffolds for the synthesis of anticancer agents in the literature (Rouge et al, 2010;Nimse ve Kim, 2013;Santos et al, 2015;Yousaf et al, 2015;Naseer et al, 2017;Yilmaz et al, 2020;An et al, 2021;Zhou et al, 2021). Due to their multiple derivatization possibilities, different functional groups that have anti-tumor properties can easily be incorporated at their lower/upper rim (de Fátima et al, 2009;Rodik et al, 2009;Dings et al, 2013;Saluja ve Sekhon, 2013;Läppchen et al, 2015;Yousaf et al, 2015;An et al, 2016;An et al, 2019;Rego ve ark., 2019).…”
Section: Introductionmentioning
confidence: 99%